Survey Indeks Entomologi dan Identifikasi Larva Aedes Aegypti di Kelurahan Pampang Kecamatan Panakukkang Kota Makassar - Abd Gafur Djafri; Ulfa Sulaeman; Hasriwiani Habo Abbas; Ummul Istiqamah; Muh. Saleh; Rusdiyah Rusdiyah (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2024)
One effort to control Aedes aedes. mosquitoes is by knowing the entomological index. The entomological index is an indicator of the density of Aedes aegypti larvae in a particular settlement which is an important consideration in determining effective vector control efforts. The success of larva monitoring is seen from the House Index (HI), Container Index (CI), Breteau Index (BI) and Larval Free Rate (ABJ), because these entomological indices are used to monitor the population density of Aedes spp in the spread of the dengue virus. The problem in this service is how to reduce the high number of dengue fever cases. This community service is to determine the larval density of the House Index, Container Index, and Breteau Index. The service methods used are surveys and observations. The results of the larval survey in Pampang subdistrict showed that the HI, CI and BI values ​​in Pampang subdistrict were respectively 26% (DF=4), 14.36% (DF=4) and 27.45 (DF=4) in the density category. moderate, while the larvae free rate (ABJ) is 79%, which still does not meet the Environmental Health Quality Standards standards in an area described as having an ABJ of less than 95%.